Montaigne ve Ahmet Haşim in Denemelerinde Aşk ve Kadın Üzerine Karşılaştırmalı Bir İnceleme - Gülşen, Hacer (My University, 2013)
In this article the point of views of Montaigne, the French author and essayist and Ahmet Hasim, one of the masters of Turkish Literature about love and woman are discussed. The French essayist Montaigne wrote only one single work on this topic and named this “Essais” and became famous of the essays. Ahmet Hasim is one of the important poets and essayists of the Turkish Literature. In this article, it is aimed to analyse Montaigne’s and Ahmet Hasim’s private lives and Works by referring to the women they loved

Bu makalede, Fransız deneme yazarı Montaigne’in ve Türk edebiyatının önemli sanatkârlarından Ahmet Haşim’in, aşka ve kadına bakış açıları ele alınmaktadır. Fransız deneme yazarı Montaigne, bütün hayatı boyunca yalnızca essais -“Denemeler” adını verdiği tek bir eser yazmış, deneme türünün öncü ismi olarak dikkat çekmiştir. Ahmet Haşim ise, Türk edebiyatının önemli şair ve deneme yazarlarındandır. Makalede Montaigne’in ve Ahmet Haşim’in eserlerindeki ve hayatlarındaki kadınlara gönderme yapılacak sanatkârların, aşk ve kadınlar hakkındaki düşünceleri, Sanatkâra dönük eleştiri anlayışı çerçevesinde karşılaştırmalı olarak incelenecektir.
Keywords: Ahmet Haşim; Montaigne; Türk Edebiyatı; Fransız Edebiyatı; Kadın; Turkish Literature; French Literature; Woman